Towards a Theory of Imagining Places: Collective Imagination and the Process of Inscribing Sites - Mozaffari, Ali (Society of Architectural Historians, Australia and New Zealand, 2010)
I propose to conceptualize the relationship between imagination and sites of collective identity, such as national architectural monuments, using as my case study, the Persepolis palace complex (canst. started 518-515 B.C.), the ceremonial capital of the Achaemenid Dynasty (559-330 B.C.) located near the city of Shiraz, south of Iran and presently an archaeological park. The history of Persepolis may be conceptualized in three periods: firstly. as a ceremonial place wt1ere royal rituals were held; secondly when, after its destruction in 330 B.C. by Alexander the Great, its factual history was forgotten while its connotations for the collective was relegated to traditional mythology and the site was ascribed a different set of mythic and sacred characteristics, and finally, from the mid-sixteenth century, when it was gradually reconnected with the Achaernenids and ultimately, in the twentieth century, became a national(ist) monument and a site of ideological contention. In discussing Persepolis, I will specifically address how it has been inscribed with meaning through Collective Imagination, through which people inscribe significant sites with 'identity narratives' -their shared story of actors, places, and events, a recognisable narrative with which they can identify collectively as 'we'. Identity narratives may be myth-histories, or a combination of factual and fictive histories. They suggest a cultural origin through which a community is bounded and differentiated.The theoretical framework articulated in this paper demonstrates that places are the outcome of a process of connecting identity narratives with empirical sites, a process which I refer to as inscription. Inscription suggests that, as collective imagination is subject to transformations and potential manipulations, places are mutable and in a state of flux. My paper demonstrates different relationships between places and architectural sites through history, relationships that are mediated through a syncretic and composite imagination, the Collective Imagination.